The Role of Attic Dusts in the Measurement of Urban Background Pollution: Investigation of Organic Pollutants From the City of Szeged (Hungary) - Csányi, Katalin; Farsang, Andrea (Journal of Central European Green Innovation, 2022)
We collected attic dust samples in the city of Szeged during 2020 and 2021. We selected 6 sampling points, an important aspect in their selection was whether there was an agricultural area nearby. The points were scattered throughout the city: downtown (control point), Újszeged, and suburban areas. The instrumental analysis of the collected dust samples was carried out by the accredited Environmental Analytical Laboratory of Green-Park 2000 Kft. in Miskolc. The laboratory tested the dust samples for 189 semivolatile organic compounds by GC-MS. The measured concentrations were compared with the limit values in the current legislation. In our results, the concentrations of most pesticides were below the limit of detection (LOQ). The "B" contamination limit was exceeded only by the concentration of persistent pesticides used in the past (p,p-DDT, methoxychlor, tetradifon). Our results clearly show the influence of the proximity of agricultural areas on the development of pesticide residue concentrations: pesticide concentration values are low in the city center and increase towards the edge of the city. Although most pesticides that showed concentrations above the pollution limit have already been banned, due to their long half-life they can still be detected. Overall, undisturbed attics can be an "archive" of atmospheric dust. It is a simple, fast and cheap sampling method. Rooftop dust testing is suitable for assessing the population’s exposure to pollutants, monitoring and mapping the spatial distribution of pollutants in the air and even determining potential source areas.